The potential for integrating school bus and public transport in Aragón, Spain - Badía Lázaro, Ricardo (Geographicalia, 2017)
This paper explores the advantages and the potential of integrating the school transport routes in the public transport network in the region of Aragón (Spain). For this propose I have compiled information about the departure points, destination points and the basic characteristics of all the routes. The results show the incipient appearance of two different integrated models. The first one corresponds to the integrated route whose main advantage is the improvement in the accessibility of services for the rural population. The second model is public transport routes with booked seats in which the main benefits are their lower cost and an improvement in the profit of public transport companies. These models still cover a small part of the demand so taking into account their advantages they have a great potential for expansion.
Keywords: Accessibility; educational center; school transport; rural transport; transport network.